(untitled) (EUROPEAN AND ASIAN LAW REVIEW, 2024)
The author analyzes the creative legacy of the founder of the Ural School of Legal Theory, his ideas about the legal progress of mankind and the prospects for the legal development of Russia. The substantive (natural law) and technical-legal (instrumental) criteria of progress, as well as the main stages of legal development, which were put forward by S. S. Alekseev, are considered in detail. The proposed design of the mechanism of the ascending development of the human race is investigated. Special attention is paid to his ideas about the legal future of Russia, about the purpose, strategy of reforming the country’s political and legal system, the main guidelines and the special mission of private law.